THE USING OF PICTURE STORY BOOKS TO INCREASE THE SPEAKING STUDENTS’ ABILITY IN STKIP BINA INSAN MANDIRI SURABAYA - Sulistiyani, Sulistiyani (Buana Pendidikan, 2018)
This study departs from the background of the need for using of the picture story book in improving the reading interest of students as one of the ways and creativity of teachers in the learning process in STKIP Bina Insan Mandiri. The purpose of this study is to describe the using of picture story book so as to improve the speaking skills of STKIP Bina Insan Mandiri. The students of English Education department. This type of research used classroom action research conducted in STKIP Bina Insan Mandiri Surabaya with 2 cycles which each cycle is conducted through 2 meetings. In the first cycle is some children are not yet accustomed in learning activities using picture story book so that speaking skills have not been too visible increase significantly. In the first cycle speaking skills earn 42% of the total number of students, and in the second cycle of reading interest of children increased to 81%. It can be concluded that learning by using picture story book can improve the speaking skills in STKIP Bina Insan Mandiri Surabaya.